Enhancing Technical Q&A Forums with CiteHistory - Fourney, Adam; Morris, Meredith Ringel (Proceedings of ICWSM 2013, 2013)
Software engineers often use Q&A forums like Stack Overflow and MSDN to ask and answer technical questions. Through a survey study and web browser log analysis, we find that both askers and answerers of technical forum questions typically conduct extensive online research before composing their posts. The inclusion of links to these research materials is beneficial to the forum participants, though post authors do not always include such citations. Based on these findings, we developed CiteHistory, a browser plugin that simplifies the process of including relevant search queries and URLs as bibliographic supplements to forum posts, and supports information re-finding for post authors. We discuss the results of a two-week deployment of CiteHistory with professional software engineers, which demonstrated that CiteHistory increased reference inclusion in posts, and offered auxiliary benefits as a personal research tracker.
You can download the CiteHistory plugin at http://research.microsoft.com/en-us/um/redmond/projects/citehistory/